Quantitative Imaging in Muscle Diseases with Focus on Non-proton MRI and Other Advanced MRI Techniques - Weber, Marc-Andre; Nagel, Armin Michael; Kan, Hermien E.; Wattjes, Mike P. (Seminars in Musculoskeletal Radiology, 2020)
The role of neuromuscular imaging in the diagnosis of inherited and acquired muscle diseases has gained clinical relevance. In particular, magnetic resonance imaging (MRI), especially whole-body applications, is increasingly being used for the diagnosis and monitoring of disease progression. In addition, they are considered as a powerful outcome measure in clinical trials. Because many muscle diseases have a distinct muscle involvement pattern, whole-body imaging can be of diagnostic value by identifying this pattern and thus narrowing the differential diagnosis and supporting the clinical diagnosis. In addition, more advanced MRI applications including non-proton MRI, diffusion tensor imaging, perfusion MRI, T2 mapping, and magnetic resonance spectroscopy provide deeper insights into muscle pathophysiology beyond the mere detection of fatty degeneration and/or muscle edema. In this review article, we present and discuss recent data on these quantitative MRI techniques in muscle diseases, with a particular focus on non-proton imaging techniques.
CRIS-Team WoS Importer:2020-10-16